Diseño de un emulgel fitocosmético a partir del aceite de la semilla de Salvia hispánica L. (chía) y ácido hialurónico - Celi Cárdenas, Milena Del Rosario; Fajardo Murillo, María Belén (My University, 2024)
Chia oil is distinguished by its high content of essential fatty acids and the presence of antioxidant compounds, such as tocopherols and polyphenols. Phytocosmetics emerge as an attractive alternative, incorporating compounds of plant origin for skin care. Thus, emulgel offers important benefits for the topical application of medications as an advanced pharmaceutical form. Hyaluronic acid has become an essential ingredient in cosmetology, due to its excellent compatibility and the multiple benefits it offers to the skin. For this reason, the purpose of this work was to design an emulgel for phytocosmetic purposes, from the seed oil of Salvia hispánica L. (chia), and hyaluronic acid using relevant statistical and technological methods. For the development of the research, chia oil supplied by the Ecuadorian company Chakra Seed Akasha Food Rachel Sait Co was used, which was completed as a quality control where similar values ​​reported in the literature were obtained, such as pH of 5.09 ± 0.428, refractive index of 1.4353 ± 0.0826, density of 0.97 ± 0.08 g/ml.From these results, the formulation of an emulgel was developed using a mixture with restrictions, in which the interaction between carbopol 940, tween 80 and mineral oil was evaluated. To prepare it, first the emulsion was prepared, whose oil phase contained mineral oil, while the aqueous phase included tween 80, methyl paraben, propyl paraben, ethanol and distilled water. In parallel, a carbopol-based gel was formulated, combining it with distilled water and adjusting the pH with triethanolamine. Finally, the emulsion was incorporated into the gel in a 1:1 ratio, thus obtaining the final emulgel. pH and extensibility are taken into account as response variables. The results obtained for pH were validated due to its proximity to the pH of the skin, which approaches 4 to 6. When the acidity of the skin is altered, the effectiveness of its protective barrier is reduced. The Jamovi statistical program in version 2.4.8.0 was used, focusing on pH and extensibility, working with 8 experiments. A sensory evaluation was carried out through surveys applied to 41 seventh and ninth semester students. Professors from the Biochemistry and Pharmacy majors also participated, which showed good acceptance. Finally, three batches of formulation 5 were prepared, which presented optimal organoleptic properties and a pH of 4.15, which suggests good compatibility with the skin. Centrifugation tests and freezing-thawing tests were also performed. The emulgel has a soft texture, is absorbed quickly, does not cause irritation and maintains adequate viscosity and extensibility. The result of this study was satisfactory. The development of this cosmetic product was carried out based on chia phytocosmetic emulgel and hyaluronic acid with nutritional properties to improve the skin, using natural resources, standing out in formulation 5 for its high sensory acceptance and its physical stability in preliminary tests.
El aceite de chía se distingue por su alto contenido de ácidos grasos esenciales y la presencia de compuestos antioxidantes, como tocoferoles y polifenoles. Los fitocosméticos surgen como una alternativa atractiva, incorporando compuestos de origen vegetal para el cuidado de la piel. Así, el emulgel ofrece importantes beneficios para la aplicación tópica de medicamentos como una forma farmacéutica avanzada. El ácido hialurónico se ha convertido en un ingrediente esencial en cosmetología, debido a su excelente compatibilidad y sus múltiples beneficios que ofrece con la piel. Por esta razón, el propósito de este trabajo fue diseñar un emulgel para fines fitocosméticos, a partir del aceite de la semilla de Salvia hispánica L. (chía), y ácido hialurónico mediante métodos estadísticos y tecnológicos pertinentes. Para el desarrollo de la investigación se utilizó el aceite de chía suministrado por la empresa ecuatoriana Chakra Seed Akasha Food Rachel Sait Co, a los cuales se terminó como control de calidad donde se obtuvieron valores similares reportados en la literatura, como son pH de 5,09 ± 0,428, índice de refracción de 1,4353 ± 0,0826, densidad de 0,97 ± 0,08 g/ml. A partir de estos resultados, se desarrolló la formulación de un emulgel utilizando una mezcla con restricciones, en la que se se evaluó la interacción entre carbopol 940, tween 80 y aceite mineral. Para su elaboración, primero se preparó la emulsión, cuya fase oleosa contenía aceite mineral, mientras que la fase acuosa incluá tween 80, metilparabeno, propilparabeno,etanol y agua destilada. Paralelamente, se formuló un gel a base de carbopol, combinándolo con agua destilada y ajustando el pH con trietanolamina. Finalmente la emulsión se incorporó al gel en una proporción de 1:1, obteniendo así el emulgel final. Se toman en cuenta el pH y la extensibilidad como variables de respuestas. Los resultados obtenidos para el pH fueron validados debido a su proximidad al pH de la piel, que se aproxima de 4 a 6 cuando se altera la acidez de la piel, se reduce la eficacia de su barrera de protección. Se utilizó el programa estadístico Jamovi en su versión 2.4.8.0 enfocándose en el pH y la extensibilidad, se trabajó con 8 experimentos. Se llevó a cabo una evaluación sensorial a través de encuestas aplicadas a 34 estudiantes de séptimo y noveno semestre, y siete profesores de la carrera de Bioquímica y Farmacia, lo cual mostró buena aceptación. Finalmente se elaboraron tres lotes de la formulación 5, los cuales presentaron propiedades organolépticas óptimas y un pH de 4.15, lo que sugiere una buena compatibilidad con la piel. También se les realizó pruebas de centrifugación, test de congelación-descongelación. El emulgel posee una textura suave, se absorbe rápidamente, no causa irritación y conserva una viscosidad y extensibilidad adecuadas. Se llevó a cabo el desarrollo de este producto cosmético a base de emulgel fitocosmético de chía y ácido hialurónico, utilizando recursos naturales, destacándose la formulación 5 por su alta aceptación sensorial y su estabilidad física en los ensayos preliminares.
Keywords: SALVIA HISPÁNICA (CHÍA),; ÁCIDO HIALURONATO; EMULGEL; FITOCOSMÉTICOS